Examining the Impact of Transformational Leadership on Employees’ Intrapreneurship Intentions - Nithyapratab, Senthilkumaran (Digital Repository of Theses - SSBM Geneva, 2025)
In an increasingly competitive business environment, employee intrapreneurial intent is now a strategic priority for organizations seeking innovation and sustainability into the future. The study aims to understand the role of transformational leadership in influencing employees’ intrapreneurial intentions in terms of its four essential components of individualized consideration and intellectual stimulation, idealized influence, and inspirational motivation. The research also looks into the significance differences of gender, marital status and age on the relationship between transformational leadership and intrapreneurial intentions. Data from employees from various industries were analyzed quantitatively so as to explore how these dimensions of leadership plus demographics influence the tendency of employees to vent their entrepreneurial activities within the organizational setting. In the competitive world of corporate business, motivating employees toward intrapreneurial intent becomes more a priority among organizations looking for innovation and longevity. The results indicate that transformational leadership has a significant positive impact on intrapreneurial intentions of employees (R² = 0.494, p = 0.000), which means that leaders with transformational approach are able to improve the willingness of the employees to innovate and take actions for initiation. Of the four components of transformational leadership, most potent are individualized consideration (R² = 0.386, p = 0.000) followed by intellectual stimulation (R² = 0.418, p = 0.000), ie, a leader who stimulates people to think differently and actively engage them in problem-solving, along with personalized support from a leader would have a conducive environment for intrapreneurship. Idealized influence (R²= 0.357, p =0.000) is also very influential and indicates role that leaders should play as ethical role models and inspire people by their vision and the integrity of those around them. Relatively less in power is inspirational motivation R² = 0.191, p=0.000, but it brings attention to an important factor that motivates people, hence making great strides to enhance the confidence and enthusiasm of employees toward entrepreneurial activities. The gender and age effects have also been established in the present study and found to be significantly different in determining intrapreneurial tendencies. While analyzing the results concerning gender, findings revealed that male employees show higher intrapreneurial inclination as compared to female employees, which may be due to difference in risk-taking propensity and perceived organizational support. Age also tends to have a significance difference, younger employees having more intrapreneurial intentions than older employees, which may imply that people at the earlier stages of their career are more responsive to innovation and risk, while older employees are more inclined towards job stability and well-laid work design. Thus, the above findings imply the necessity of devising differentiated approaches to leadership among demographically distinct groups to yield efficient and sufficient transformational leadership adoption across the different employee profiles.